miR-802 inhibits the epithelial-mesenchymal transition, migration and invasion of cervical cancer by regulating BTF3 - Wu, Xiuhui (Mol Med Rep, 2020)
MicroRNA (miR)-802 has been discovered to be involved in the occurrence and development of numerous types of tumor; however, studies into the role of miR-802 in cervical cancer are limited. Therefore, the present study aimed to investigate the regulatory effects of miR-802 in cervical cancer cells. miR-802 expression levels in cervical cancer tissue and cells were analyzed using reverse transcription-quantitative (RT-q)PCR, a dual-reporter luciferase activity assay was used to identify the direct target gene of miR-802, and RT-qPCR and western blotting were performed to determine the relationship between miR-802 and basic transcription factor 3 (BTF3). Cell viability, and migration and invasion were analyzed using Cell Counting Kit-8 and Transwell assays, respectively. Finally, the expression levels of metastasis-associated proteins, N-cadherin and E-cadherin, were determined using RT-qPCR and western blotting. Decreased expression levels of miR-802 were found in cervical cancer tissues and cells, and the overexpression of miR-802 inhibited cell viability, migration and invasion. Moreover, miR-802 was discovered to directly target BTF3 to inhibit its expression. Notably, the overexpression miR-802 markedly reversed the promotive effect of BTF3 on cell viability, in addition to the migratory and invasive abilities of the cells. Simultaneously, the overexpression of miR-802 significantly suppressed epithelial-mesenchymal transition, and the expression levels of matrix metallopeptidase (MMP)2 and MMP9 in cells through regulating BTF3. In conclusion, the present study revealed that miR-802 may suppress cervical cancer progression by decreasing BTF3 expression levels, indicating that it may represent a potential therapeutic target for the treatment and prognosis of patients with cervical cancer.